Bcl-2-functionalized ultrasmall superparamagnetic iron oxide nanoparticles coated with amphiphilic polymer enhance the labeling efficiency of islets for detection by magnetic resonance imaging - Yang B (Dove Medical Press, 2013)
Bin Yang,1 Haolei Cai,1 Wenjie Qin,1 Bo Zhang,1 Chuanxin Zhai,2 Biao Jiang,3 Yulian Wu1 1Department of Surgery, 2nd Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China; 2State Key Lab of Silicon Materials and Department of Materials Science and Engineering, Zhejiang University, Hangzhou, People’s Republic of China; 3Department of Radiology, 2nd Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China Abstract: Based on their versatile, biocompatible properties, superparamagnetic iron oxide (SPIO) or ultrasmall superparamagnetic iron oxide (USPIO) nanoparticles are utilized for detecting and tracing cells or tumors in vivo. Here, we developed an innoxious and concise synthesis approach for a novel B-cell lymphoma (Bcl)-2 monoclonal antibody-functionalized USPIO nanoparticle coated with an amphiphilic polymer (carboxylated polyethylene glycol monooleyl ether [OE-PEG-COOH]). These nanoparticles can be effectively internalized by beta cells and label primary islet cells, at relatively low iron concentration. The biocompatibility and cytotoxicity of these products were investigated by comparison with the commercial USPIO product, FeraSpin™ S. We also assessed the safe dosage range of the product. Although some cases showed a hypointensity change at the site of transplant, a strong magnetic resonance imaging (MRI) was detectable by a clinical MRI scanner, at field strength of 3.0 Tesla, in vivo, and the iron deposition/attached in islets was confirmed by Prussian blue and immunohistochemistry staining. It is noteworthy that based on our synthesis approach, in future, we could exchange the Bcl-2 with other probes that would be more specific for the targeted cells and that would have better labeling specificity in vivo. The combined results point to the promising potential of the novel Bcl-2-functionalized PEG-USPIO as a molecular imaging agent for in vivo monitoring of islet cells or other cells. Keywords: USPIO, MRI, beta cells, nanoparticle functionalization, islet transplantation, cell tracing